Innate immunity mediates follicular transport of particulate but not soluble protein antigen. - Link, A; Zabel, F; Schnetzler, Y; Titz, A; Brombacher, F; Bachmann, M (2012)
Ag retention on follicular dendritic cells (FDCs) is essential for B cell activation and clonal selection within germinal centers. Protein Ag is deposited on FDCs after formation of immune complexes with specific Abs. In this study, by comparing the same antigenic determinant either as soluble protein or virus-like particle (VLP), we demonstrate that VLPs are transported efficiently to murine splenic FDCs in vivo in the absence of prior immunity. Natural IgM Abs and complement were required and sufficient to mediate capture and transport of VLPs by noncognate B cells. In contrast, soluble protein was only deposited on FDCs in the presence of specifically induced IgM or IgG Abs. Unexpectedly, IgG Abs had the opposite effect on viral particles and inhibited FDC deposition. These findings identify size and repetitive structure as critical factors for efficient Ag presentation to B cells and highlight important differences between soluble proteins and viral particles.